ANALISIS PENYALURAN DANA BANTUAN UMKM (BANPRES) DINAS KOPERASI KOTA MEDAN TERHADAP PENGUSAHA MIKRO KECIL DI KOTA MEDAN: ( Studi Kasus Para Pengusaha Mikro di Kecamatan Medan Timur ) - Dewi Sundari; M. Guffar Harahap (Universitas Pahlawan Tuanku Tambusai, 2022)
The impact that has occurred due to the Covid-19 Pandemic is very much felt for all Indonesian people and society, especially for people who earn from micro-enterprises who are getting worse day by day. To overcome this problem and minimize it, the government takes an action. One of the steps taken by the government is to provide UMKM assistance (Banpres) so that the community can be supported and assisted in saving and maintaining their business during the Covid-19 Pandemic. This research aims to determine the effect of this Banpres assistance on the UMKM community affected by Covid-19. To find out how the government works specifically for the City Cooperative Service in carrying out assistance programs to the UMKM community. The object of research is the UMKM community in Medan City (Case Study of the Glugur Darat Community, East Medan District). Based on the research in the field, it can be concluded that the Banpres Grant Program ran smoothly and was very successful in its distribution because it was received directly by the community of micro business actors through banks that had been appointed by the Cooperatives Service. Which is expected by the government because basically most of the UMKM recipients do not use these funds for business development, but the aid funds are allocated or used for the consumptive needs of the community. Keywords: Banpres, Cooperative Service, UKM